Physical Activity as a Mediator in the Relationship Between Oral health status and Depression Prevalence in Older Adults - Min-Jun Kim; Taewan Kim; Yoonhwan Kim; Donghyun Kim (운동과학)
PURPOSE This study aimed to investigate the mediating role of physical activity in the association between oral health and depression among Korean individuals aged ≥65 years. METHODS Data were obtained from the 2023 Korea Community Health Survey, comprising 68,806 participants aged ≥65 years. Oral health was assessed using two self-reported indicators: perceived oral health status and chewing discomfort. According to the revised edition of the Physical Activity Guidelines for Koreans, physical activity was categorized into three levels (inactive, insufficient, and sufficient). Depression was defined as a score of 10 or higher on the Patient Health Questionnaire-9. The mediating effect of physical activity on the relationship between oral health and depression was analyzed using the PROCESS macro (Model 4). RESULTS Poorer oral health was significantly associated with a higher level of depression (path a, β=-0.019, p<.001), while higher levels of physical activity were inversely associated with depression (path b, β=-0.083, p<.001). Furthermore, physical activity partially mediates the relationship between oral health and depression (indirect effect, β=0.002, 95% CI=0.001 to 0.002), accounting for approximately 0.6% of the total effect. CONCLUSIONS These findings indicate that engaging in regular physical activity may partially reduce the risk of depression resulting from deteriorating oral health, suggesting its potential as a complementary strategy for the prevention and management of depression associated with declining oral health.